1987
DOI: 10.1172/jci112773
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the platelets in paroxysmal nocturnal hemoglobinuria with complement. Relationship to defects in the regulation of complement and to platelet survival in vivo.

Abstract: The blood cells of patients with paroxysmal nocturnal hemoglobinuria (PNH) have abnormal interactions with complement. The activity of the alternative pathway C3 convertase on the platelets of 9 out of 19 patients with PNH was elevated. 10 patients had C3 convertase activity within the normal range even though 80-95% of their platelets lacked the complement regulatory protein decay accelerating factor (DAF) that is absent from the affected blood cells in PNH. PNH and normal platelets released factor H when C3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…This platelet-associated factor H resides in ␣ granules, is functionally active, and is released upon complement activation or other stimuli (63,64). Our data show that rodent platelets are different from their human counterparts as they contain factor H on their surface.…”
Section: Table IImentioning
confidence: 80%
“…This platelet-associated factor H resides in ␣ granules, is functionally active, and is released upon complement activation or other stimuli (63,64). Our data show that rodent platelets are different from their human counterparts as they contain factor H on their surface.…”
Section: Table IImentioning
confidence: 80%
“…This activity could be removed from the sonicates with antiserum to factor H (17). Studies from this laboratory on the activity of the alternative pathway C3 convertase on the platelets of patients with PNH demonstrated that not all patients have the increased C3bBb activity that might be expected from platelets deficient in DAF (15). In studies reported here we demonstrate that normal human platelets contain factor H, which can be secreted from platelet a granules and can regulate the activity of platelet-bound C3bBb.…”
mentioning
confidence: 57%
“…min at 370C with 1 mg of C3 and cobra venom factor-factor Bb complexes. These complexes were prepared using purified cobra venom factor, factor B, and factor D as described (15). The amount of platelet-bound C3b at this step was measured by monoclonal anti-C3c antibody binding assay similar to that described (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations